2021
DOI: 10.1002/art.41571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Deaths, and Disability‐Adjusted Life Years Due to Musculoskeletal Disorders for 195 Countries and Territories 1990–2017

Abstract: Objective To report the levels and trends of prevalence, deaths, and disability‐adjusted life years (DALYs) due to musculoskeletal disorders, categorized as low back pain, neck pain, osteoarthritis (OA), rheumatoid arthritis (RA), gout, and other musculoskeletal disorders, across 195 countries and territories from 1990 to 2017 according to age, sex, and Sociodemographic Index (SDI; a composite of sociodemographic factors). Methods Data were obtained from the Global Burden of Disease (GBD) Study 2017. The fatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 33 publications
(61 reference statements)
5
162
1
3
Order By: Relevance
“…The global burden of disease study 2017 showed a large burden of musculoskeletal disorders, with approximately 1.3 billion cases globally. 49 Of these, the knee OA is among the most disabling musculoskeletal conditions. Inflammation is regarded as an important feature of early OA, and the altered inflammatory state induced by mechanical stress is considered an underlying cause.…”
Section: Discussionmentioning
confidence: 99%
“…The global burden of disease study 2017 showed a large burden of musculoskeletal disorders, with approximately 1.3 billion cases globally. 49 Of these, the knee OA is among the most disabling musculoskeletal conditions. Inflammation is regarded as an important feature of early OA, and the altered inflammatory state induced by mechanical stress is considered an underlying cause.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders are the leading cause of years lived with disability and the fifth most common cause of disability-adjusted life years worldwide in 2017 according to estimates from the Global Burden of Diseases [1][2][3]. Musculoskeletal disorders cause pain and functional disability [4][5][6], and their burden on individuals and society has been increasing worldwide [2,3,7]. Therefore, public interest in musculoskeletal disorders during the coronavirus disease 2019 (COVID-19) pandemic should be assessed to develop effective measures for the management of musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…There are globally 1.3 billion cases of musculoskeletal disorders and over 121,000 deaths from such disorders, as well as nearly 139 million disability-adjusted life years, or the number of years lost due to ill-health, disability or early death [43]. Globally, the proportion cases in are led by the low back pain (37%); followed by "other"…”
Section: Arthritis Drug Designmentioning
confidence: 99%